Traumatic Neuroma - An unforeseen lesion subsequent to simple extraction - A Anuradha; VVS Ram Prasad; Vijay Srinivas; Bina Kashyap; Suvarna (Wolters Kluwer Medknow Publications, 2012)
Traumatic neuromas are relatively rare entities that characteristically arise following surgery or trauma. They are usually accompanied by pain of typical neuralgic type. We present an interesting case of traumatic neuroma of mental nerve following tooth extraction, which clinically presented as ear pain.